Anatomía de la madera de ocho especies con importancia en las artesanías del estado de Michoacán - Perez Olvera, Carmen de la Paz (Instituto de Ecología, A.C., 1993)
This paper is a contribution toward the knowlege of wood anatomy of eight species of trees used for handicraft goods produced in the state of Michoacan (Mexico): Gyrocarpus jatrophifolius, Bocconia arborea, Lysiloma acapulcensis, Lysiloma microphylla, Platymiscium lasiocarpum, Cedrela dugesii, Cordia elaeagnoides, Ehretia latifolia. Descriptions of esthetic aspects and of wood structure are made. Statistical univariate analysis of measured elements is applied. Wood characters of the trees are correlated with their real and potential use.